Philosophic representations of concepts “space” and “time”: from physics to music - Tararoyev, Y. V.; NetzvetayТ. V. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2019)
The article discusses various philosophical ideas about space and time. It is indicated that these representations are systemic and hierarchical. The «pyramid» of these ideas is based on the most fundamental, physical concepts of the objective properties and laws of physical reality, such as the relationship of duration and the relationship of length. At the next «stage» they are complemented by the specifics of chemical and biological processes in living matter. The notions of social space and time are even more complex, which are due to the more complex nature of social processes and phenomena. However, all three groups of ideas (physical, biological and social space and time) reflect the objective properties and laws of reality. The next group of views reflects the subjective perception of duration and extent. They function on the basis of objective representations, but fix the features of the perception of the subject acting in a certain cultural «field». These primarily include psychological space and time. They have a complex structure and are associated with the daily life of the individual, which is due to both biological and social factors. The properties of this space and time are set by sensual and rational abilities of cognition, and it is the psychological space and time that serves as the ontological basis for even more complex forms of perception – artistic space and time. Art space and time are attributes of artistic fictional being, with the help of which the artistic image gets the opportunity for development and its holistic perception. A subspecies of artistic space and time – musical space-time continuum. This variety exists within a certain aspect of human artistic activity – musical art. Music is a temporary type of art; formally, music can be represented as an acoustic stream of sounds that is intonationally and rhythmically organized and unfolding in time, having a complex structure and carrying a certain semantic and communicative load. Musical time or time in music is a complex and multifaceted concept. The space in music is the visual and aesthetic images of the human imagination, caused by sound effects, these are internal metaphorical ideas about the properties of space, corresponding to a specific semantic context. Thus, speaking of music space and time, it can be argued that they are the «conceptual pinnacle» of the development of ideas about space and time in general and include many of the most important properties of other forms and types of space and time. All these forms lead their "genealogy" from the concepts of physical space and time.